1855 Ill. Laws, 25 - (:unkn) unknown (My University, 1855)
An Act To Incorporate the Town of Daville, § 16: Granted the town of Daville the power and authority to regulate the storage of tar, pitch, rosin, gun powder, and other combustible materials.
Keywords: GUNPOWDER - STORAGE